2012
DOI: 10.1007/s13311-012-0110-4
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1beta Causes Fluoxetine Resistance in an Animal Model of Epilepsy-Associated Depression

Abstract: Depression represents a common comorbidity of epilepsy and is frequently resistant to selective serotonin reuptake inhibitors (SSRI). We tested the hypothesis that the SSRI resistance in epilepsy associated depression may be a result of a pathologically enhanced interleukin-1β (IL1-β) signaling, and consequently that the blockade of IL1-β may restore the effectiveness of SSRI. Epilepsy and concurrent depression-like impairments were induced in Wistar rats by pilocarpine status epilepticus (SE). The effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(42 citation statements)
references
References 54 publications
1
39
0
2
Order By: Relevance
“…In 2012, Pineda et al [72] treated Wistar rats with comorbid epilepsy and depression with selective serotonin reuptake inhibitors (SSRIs) and IL-1 receptor antagonists (IL-1Ra); the results showed that fluoxetine monotherapy was ineffective and IL-1Ra reversed anhedonia and partially improved other depressive disorders. The combination of the two drugs eliminated all the symbolic characteristics of depression in epilepsy and improved the HPA axis.…”
Section: Neuroinflammationmentioning
confidence: 99%
“…In 2012, Pineda et al [72] treated Wistar rats with comorbid epilepsy and depression with selective serotonin reuptake inhibitors (SSRIs) and IL-1 receptor antagonists (IL-1Ra); the results showed that fluoxetine monotherapy was ineffective and IL-1Ra reversed anhedonia and partially improved other depressive disorders. The combination of the two drugs eliminated all the symbolic characteristics of depression in epilepsy and improved the HPA axis.…”
Section: Neuroinflammationmentioning
confidence: 99%
“…Both clinical and animal studies have been performed in this field in order to define or find a correlation between these pathologies [4,[14][15][16][17]. Good results have also been achieved in identifying some neurobiological common basis and pharmacological correlates [18][19][20][21][22][23]. Although behavior has been experimentally studied in several models of epilepsy, only few can be regarded as animal models of epilepsy and comorbid mood disorder, namely, the genetically epilepsy-prone rats (GEPRs) [24] and some genetic models of absence epilepsy (i.e., GAERS and WAG/Rij rats) [25].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is conceivable that the disruption of IL-1β signaling in the epileptic brain and subsequent normalization of 5-HT 1A autoreceptor function would restore the effectiveness of SSRI. This suggestion has been confirmed directly, whereby adjunctive therapy with a low, ineffective on its own, dose of IL-1RA renders fluoxetine therapeutically effective in animals with epilepsy-associated depression [193].…”
Section: Brain Inflammationmentioning
confidence: 84%